2004
DOI: 10.1093/brain/awh039
|View full text |Cite
|
Sign up to set email alerts
|

Raised parenchymal interleukin-6 levels correlate with improved outcome after traumatic brain injury

Abstract: Previous studies have suggested that an increased production of the pro-inflammatory cytokines interleukin-6 (IL-6) and interleukin-1beta (IL-1beta) can influence patient outcome following a severe head injury. However, these studies have relied upon measurements of cytokine levels in CSF or serum, rather than the brain parenchyma itself. Recently, a method of intracranial microdialysis has been developed which permits the efficient recovery of macromolecules from the parenchyma. We have used this technique to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
4
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(125 citation statements)
references
References 34 publications
5
109
4
4
Order By: Relevance
“…1,2,6,8,9,[11][12][13]30,32 Similar to TNF-a, it is detectable by 1 hour postinjury and peaks in brain parenchyma at approximately 2-8 hours. 32 However, unlike TNF-a, particularly related to the DAI model, IL-6 levels do not depend on the injury model, and this is a more sensitive marker.…”
Section: Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,6,8,9,[11][12][13]30,32 Similar to TNF-a, it is detectable by 1 hour postinjury and peaks in brain parenchyma at approximately 2-8 hours. 32 However, unlike TNF-a, particularly related to the DAI model, IL-6 levels do not depend on the injury model, and this is a more sensitive marker.…”
Section: Cytokinesmentioning
confidence: 99%
“…Similarly, the role of proinflammatory (interleukin [IL]-6, IL-1, tumor necrosis factor-a [TNF-a]) and antiinflammatory (IL-4, IL-10, transforming growth factor) cytokines has been validated in recent trials. 1,2,6,8,9,[11][12][13]22,26,27,30,36 More recently, posttraumatic suppression of the hypothalamic-pituitary-adrenal axis and an increase in cytokine-mediated peripheral aromatase activity, leading to an imbalance in sex steroid (estrogen [Eg], progesterone [Pg], and testosterone) serum levels, have been areas of active interest for precise understanding of the mechanisms involved. 5,15,23,25,29 Most of the recent literature deals with these biomarkers in isolation, and there is a paucity of existing literature for establishing a comprehensive model dealing with all 3 domains together.…”
mentioning
confidence: 99%
“…57 An in vivo microdialysis study has shown that increased parenchymal IL-6 levels correlate with survival and GOS suggesting that IL-6 is an endogenous neuroprotective cytokine. 58 Furthermore, increased CSF levels of IL-6 have been reported to correlate with improved outcome in pediatric TBI. 59 Interestingly, induced hypothermia has no effect on IL-6 levels in children, a finding that is in contrast to that observed in adult TBI patients in which IL-6 levels were found to decrease after therapeutic hypothermia.…”
Section: Interleukin-6mentioning
confidence: 99%
“…The highly developed endothelial cell-cell (EC-EC) contacts of the BBB restrict paracellular diffusion, forcing most solute flux across the cerebral endothelium to occur by transcellular routes (Banks, 1999;Miller, 2010). Dysfunction of the BBB, and thus BBB hyperpermeability, has been implicated in the onset and/or progression of several neuroinflammatory diseases, such as traumatic brain injury, stroke, multiple sclerosis, encephalitis and Alzheimer disease (Hawkins and Davis, 2005;Winter et al, 2004;Zlokovic, 2008). Hence, understanding the mechanisms of inflammatory-mediated BBB disruption is of crucial importance.…”
Section: Introductionmentioning
confidence: 99%